Intelligent systems, AI/ML, IoT, smart grids, robotics, healthcare, and emerging innovations - Sutikno, Tole (Institute of Advanced Engineering and Science, 2026)
This editorial discusses the latest trends and emerging ideas in electrical and computer engineering. It emphasises how intelligent systems, artificial intelligence and machine learning (AI/ML), the Internet of Things (IoT), smart grids, robotics, and healthcare technologies are transforming the field. The issue highlights the integration of data-driven intelligence, adaptive control, and real-time monitoring across various applications, including industrial automation, energy management, environmental monitoring, and personalised healthcare. Key themes encompass the development of AI/ML models for predictive analytics, IoT-enabled cyber-physical systems for autonomous decision-making, robotics for both human assistance and industrial operations, and smart grids aimed at achieving sustainable and resilient energy distribution. Furthermore, emerging innovations tackle challenges related to scalability, interpretability, energy efficiency, security, and the ethical deployment of intelligent technologies. By examining these interconnected domains, the editorial underscores the increasing interplay between computational intelligence, connected systems, and societal needs, while offering suggestions for future research directions and considering the potential impact of these technologies on global industries and human well-being.